Reducing customer complaints in air conditioning installation services through lean and MRP tools: a case study - Aguilar Cevallos, Silvana Alexandra (2024)
In Latin America, the business services sector is constantly searching for continuous improvement, improving the performance of service operations and service quality. However, merchandise availability must be guaranteed to prevent stock-outs and preserve high customer satisfaction. Because of this, managing a warehouse inside a service organization is quite tricky. In this way, a model for improvement was created to address the issues raised above, combining Lean Service tools like ABC, 5S, and standardization of work with a Material Requirements Plan (MRP) to reduce the claims rate, which is currently 60 percent due to ineffective management of the tool ordering and installation processes. After implementing the pilot plan and the simulation in the Arena software, a significant variation in the claims rate could be evidenced by reducing it to 30%. This article contributes to the first validation of Lean tools in the service sector and will continue contributing to future managers with similar processes.